If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3z-4)=5(-8z+18)
We move all terms to the left:
2(3z-4)-(5(-8z+18))=0
We multiply parentheses
6z-(5(-8z+18))-8=0
We calculate terms in parentheses: -(5(-8z+18)), so:We get rid of parentheses
5(-8z+18)
We multiply parentheses
-40z+90
Back to the equation:
-(-40z+90)
6z+40z-90-8=0
We add all the numbers together, and all the variables
46z-98=0
We move all terms containing z to the left, all other terms to the right
46z=98
z=98/46
z=2+3/23
| 3/2n-3=9 | | 13=-10-z | | 0=4x^2+20 | | Y=4x^2+20 | | 185=5/2x | | 38=65x+0 | | 3x-4(x+3)=23 | | 4x3–7x2–1,B=9–4x3+8x2 | | 800=59x+354 | | 11-51=4t+4t | | 3=0.1x+1.5 | | 9=d+7/6 | | 2/3x=13/8 | | -4+5y=-4 | | -2k-7=-23 | | 0.08n+0.12n=5 | | 9x=12+9x | | 120-4y+2y=72 | | 4x+3=5x+14 | | 2x-3=22-3x | | s/7=8- | | 15x-10=-6x-(x+2)+(-x+3) | | 4(n-12)=12 | | 6=r=10 | | -3n=-30 | | 2(z-3)+(z+3)=6z | | 8x-4x-10=20 | | -2n^2-8n-42=0 | | 8x-(3x-5)=25 | | 300+.14x=200+.25x | | 10y-10=2y+70 | | 6.6=2.3+y |